Seasonal variation of bacterial load in river and lake waters of Dhaka city, Bangladesh (Bangladesh Journal of Microbiology, 2019)
Surface water is often contaminated due to human excreta and urban and industrial pollution. The increased population growth and industrialization are likely to exacerbate the situation. Microbiological analysis of waters from rivers (Turag and Buriganga) and lakes (Banani and Dhanmondi) around Dhaka city were conducted for Spring, Monsoon and Fall seasons of the year, 2016 and 2017. Total Viable Count (TVC), Total Coliform Count (TCC), Total Fecal Coliform Count (TFCC) and Total Salmonella Shigella Count (TSSC) were conducted to obtain bacterial load in both enriched and without enrichment water samples. All the Isolates were identified by microscopy, cultural characteristics and biochemical methods. Most of the water reservoirs have a decline in the bacterial load in monsoon where the microbial load of pathogens is highest during spring. Without enrichment, E. coli, Enterobacter sp., Klebsiella sp. and S. aureus were abundant, where others like Shigella sp., Proteus sp., Serratia sp., Pseudomonas sp., Acinetobacter sp., and Alcaligenes faecalis mostly exhibited growth following enrichment. Results indicate that pathogenic environmental isolates can cause serious health issue if water is left untreated or poorly treated from reservoirs within and around Dhaka city.Bangladesh J Microbiol, Volume 35 Number 2 December 2018, pp 116-121